2019
DOI: 10.1002/pip.3182
|View full text |Cite
|
Sign up to set email alerts
|

Application of semitransparent photovoltaics in transportation infrastructure for energy savings and solar electricity production: Toward novel net‐zero energy tunnel design

Abstract: Lighting subsystems account for up to 50% of the energy consumption of a typical tunnel. Day‐time lighting levels account for over two‐thirds of the total system lighting power; their periodic nature creates daily peaks in the tunnel's energy load profile. This paper studies the integration of semitransparent photovoltaic (STPV) cells into sunscreen structures installed above tunnel entrances to reduce tunnel lighting requirements and offset their day‐time lighting loads using energy generated from PVs. The el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The forestation of portal surroundings also contributes to certain metrics evaluating the sustainability of the whole tunnel (López, Grindlay & Peña-García, 2017). Other research has proposed to decrease the L20 luminance through the installation of black solar panels whose energy output can be used to power auxiliary lighting and other installations (Sun et al, 2019;Peña-García & Gómez-Lorente, 2020). A simulated view is presented in Fig.…”
Section: Strategies To Decrease the Impact Of The Lighting Installati...mentioning
confidence: 99%
“…The forestation of portal surroundings also contributes to certain metrics evaluating the sustainability of the whole tunnel (López, Grindlay & Peña-García, 2017). Other research has proposed to decrease the L20 luminance through the installation of black solar panels whose energy output can be used to power auxiliary lighting and other installations (Sun et al, 2019;Peña-García & Gómez-Lorente, 2020). A simulated view is presented in Fig.…”
Section: Strategies To Decrease the Impact Of The Lighting Installati...mentioning
confidence: 99%
“…In research [8], many methods and algorithms are presented for the proper configuration of the PV array. Semitransparent photovoltaic (STPV) cells are integrated into sunscreen structures in [9] to reduce lighting requirements. The results of using STPV show annual net energy savings of up to 7 % and electricity savings of up to 60 % during the day.…”
Section: Algorithms For Optimization and Reconfigurationmentioning
confidence: 99%
“…Much research on energy resources has been reported, including electricity generation from food waste through anaerobic digestion (Ali et al 2019 ; Rezaie and Rosen 2020 ) and hydroelectric generation (Udayakumara and Gunawardena 2018 ), and solar energy applications (Hachem-Vermette et al 2019 ; Sun et al 2019 ). These studies collectively demonstrate the importance of energy sources in discussions of sustainability, and illustrate the feasibility of such technologies in practical applications.…”
Section: Sustainability and Energymentioning
confidence: 99%
“…Such buildings are net energy generators, rather than net energy users, like most buildings today. Research on net-zero and net-positive energy buildings has been reported (Athienitis and O’Brien 2015 ; Mehrjerdi et al 2019 ; Sun et al 2019 ), while the International Energy Agency included an annex on “Towards Net-zero Energy Solar Building” and Canada launched in 2011 the Smart Net-zero Energy Buildings Strategic Research Network ( http://www.solarbuildings.ca ). The net-zero and net-positive energy building concepts can be expanded to include transportation devices that are part of the building (Garmsiri et al 2016 ; Sun et al 2019 ) and to net-zero and net-positive energy communities (Rad et al 2017 ; Hachem-Vermette et al 2019 ; Karunathilake et al 2019 ; Nematchoua et al 2021 ).…”
Section: Illustrationmentioning
confidence: 99%